2018
DOI: 10.2147/ott.s181936
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CLIC1 as a potential biomarker for oral squamous cell carcinoma: a preliminary study

Abstract: PurposeCLIC1, a member of the highly conserved class ion-channel protein family, is frequently upregulated in multiple human malignancies and has been demonstrated to play a critical role in cell proliferation, apoptosis, and invasion. However, limited is known about its expression, biological functions, and action mechanism in oral malignancies. We aimed to evaluate whether CLIC1 could be a biomarker for oral squamous cell carcinoma (OSCC).MethodsImmunohistochemistry was used to analyze the expression of CLIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
(25 reference statements)
1
18
0
Order By: Relevance
“…Recently, indeed, Thuringer et al have reported this very crosstalk between glioblastoma cells and endothelial cells that is mediated by CLIC1 released through extracellular vesicles by tumor cells and captured by endothelial cells, which are induced to sprout and form tubes in 3D matrices (34). CLIC1 has already been reported as a potential biomarker for some malignant tumors (6,10,16) and a potential therapeutic target for new treatments in cancer. Its expression in both tumor and endothelial cells may pave the way for the development of future anti-CLIC1 therapy, able to target both tumor and its associated vessels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, indeed, Thuringer et al have reported this very crosstalk between glioblastoma cells and endothelial cells that is mediated by CLIC1 released through extracellular vesicles by tumor cells and captured by endothelial cells, which are induced to sprout and form tubes in 3D matrices (34). CLIC1 has already been reported as a potential biomarker for some malignant tumors (6,10,16) and a potential therapeutic target for new treatments in cancer. Its expression in both tumor and endothelial cells may pave the way for the development of future anti-CLIC1 therapy, able to target both tumor and its associated vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the six members of intracellular chloride ion channel protein family (CLICs), CLIC1 and CLIC4 have been extensively studied regarding their involvement in tumor development (4). Indeed, CLIC1 is overexpressed in several tumor types, such as gastric cancer (5), oral squamous cell carcinomas (6) or glioblastoma (7). Recently, Barbieri et al reported that CLIC1 inhibition induces glioblastoma growth inhibition, mainly by acting on CLIC1-rich glioblastoma stem cells, decreasing their proliferation and subsequently tumor progression (8).…”
mentioning
confidence: 99%
“… 24 Xu et al detected highly expressed CLIC1 protein in the blood of patients with oral squamous cell carcinoma. After the patients were treated with surgery and chemotherapy, the expression level of CLIC1 protein was significantly reduced, 25 which suggested that CLIC1 may become a tumor therapeutic target and a biomarker for judging the therapeutic effect. In addition, CLIC1 significantly affected the prognosis of ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…TNM represents an effective clinical tool for predicting OSCC prognoses [25]. Moreover, molecular biomarkers could become a beneficial supplement to TNM for improving the predictive accuracy [26]. Also, these molecules exert key functions on OSCC progression as well as serve as novel therapeutic targets [27].…”
Section: Discussionmentioning
confidence: 99%